Out of nature : why drugs from plants matter to the future of humanity - Rogers, Kara (Tucson : University of Arizona Press, 2012)
About half of all species under threat of extinction in the world today are plants. The loss of plant biodiversity is disturbing for many reasons, but especially because it is a reflection of the growing disconnect between humans and nature. Plants have been used for millennia in traditional systems of healing and have held a significant place in drug development for Western medicine as well. Despite the recent dominance of synthetic drug production, natural product discovery remains the backbone of drug development. As the diversity of life on Earth is depleted and increasing numbers of species become lost to extinction, we continue to lose opportunities to achieve advances in medicine. Through stories of drug revelation in nature and forays into botany, human behavior, and conservation, Kara Rogers sheds light on the multiple ways in which humans, medicine, and plants are interconnected. Rogers also highlights the role that plant-based products can play in encouraging conservation and protecting the heritage and knowledge of indigenous peoples. The book delves into the complexity of biophilia--the innate human attraction to life in the natural world--and suggests that the reawakening of this drive is fundamental to expanding conservation efforts and improving medicine.--Publisher information
Plants and medicine -- Humans and plants -- The biophilia factor -- In earth's garden -- Vanishing life -- Out of nature -- Learning to coexist -- The forest for its trees
Includes bibliographical references and index.
Keywords: PHARMACOGNOSY